The Issue of Copyright Infringement in 4.0 Industrial Revolution: Indonesian Case - Nurhayati, Yati; Ifrani, Ifrani; Halim Barkatullah, Abdul; Said, M Yasir (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
Industrial revolution has substantially changed the economy and society. The fusion of technologies and information marked the fourth industrial revolution which brings about new challenges relating to protection of intellectual property, including copyrights. With regard to this, there has been several changes in the law relating to copyrights in Indonesia. The nature of copyright infringement has been changed from ordinary offense to complaint-based offense. This fundamental change undoubtedly affects the enforcement of the copyright law in Indonesia. Thus this paper aims to answer and review the legal reasoning behind the shift in offense in Copyright Law in Indonesia. This normative legal research employed a descriptive-analytic method. The result shows that the complaint-based offense is suitable in copyright protection considering that only the copyright owner knows the details of the object of the creation.